EXPLICIT BACK-CHANNEL STRATEGY TRAINING AND IMPROVEMENT OF SPEAKING SKILL: CASE OF IRANIAN EFL LEARNERS - Maliheh Yazdfazeli; Khalil Motallebzadeh; Mohammad Ali Fatemi (Universitas Kuningan, 2015)
This study explores the effect of explicit back-channel strategy training on Iranian EFL language learners success in speaking skill. Back-channels are turn taking responses uttered by the listeners. Forty homogenous learners (20 male, 20 female) were randomly assigned to four groups (2 experimental, 2 control). They were at intermediate level in terms of general English proficiency based on the results of Oxford Placement Test (OPT) and pre-test oral Proficiency Interview. After 18 sessions of treatment of back-channels for experimental groups, that were based on the methodological theory of English language teaching suggested by Doff (1990) and Harmer (1991), post- test oral proficiency test was administered for experimental and control groups. The findings of pretest and posttest oral exams revealed that EFL language learners oral performance (speaking) in experimental groups improved. The result revealed that females employed back-channels more often than males when they were participating in a conversation. The type of back-channel both genders employed the most was short utterances, such as yes, and the most used function of back-channel was request for clarification. The results of this thesis will provide language teachers, EFL language learners, researchers, material developers, and readers, useful information about the types and functions of back channels that are needed to develop speaking ability appropriately through explicit teaching.